Juridical Implications Of Child Series Marriage In Pohuwato: Uncertainty Of The Status Of Mother And Child In The Indonesian Legal System - Mohamad, Dhea Putri; Kasim, Nur Mohamad; Elfikri, Nurul Fazri (SM Institute, 2025)
This study aims to analyze the legal implications of the implementation of unregistered marriage in the context of child marriage on the legal status of mothers and children, and how it impacts the fulfillment of their civil rights in the legal system in Indonesia. The practice of unregistered marriage carried out by underage couples is still widespread in various regions, including in Pohuwato Timur Village, Marisa District, Pohuwato Regency, Gorontalo Province. Although religiously the marriage is considered valid, according to state law, a marriage without official registration does not have binding legal force. As a result, women who are married unregistered are not officially recognized as wives, and children born from the marriage only have a civil relationship with their mothers, as regulated in Article 43 of Law No. 16 of 2019 concerning Marriage. This study uses an empirical legal research method with a qualitative approach. Data were obtained through interviews, field observations, and documentation of the community and government officials in Pohuwato Timur Village, and analyzed descriptively-qualitatively. The results of the study indicate that low legal awareness in society, economic limitations, and geographical barriers are the main factors that encourage the practice of unregistered marriage among children. The legal implications are the uncertainty of the legal status of wives and children, as well as obstructed access to civil rights such as birth certificates, inheritance rights, and other legal protections. Strategic efforts are needed through legal education, ease of marriage dispensation and marriage confirmation procedures, and the active role of village governments and judicial institutions in ensuring protection for mothers and children from unregistered marriage practices.